An?lise de desempenho de t?cnicas de modula??o adaptativa, FEC adaptativo e t?cnicas h?bridas em canais com desvanecimento rayleigh - Bandiri, Sabi Yari Mo?se (2015)
Wireless networks suffer fading, effects such as Rayleigh fading, which affect their performance and consequently the quality of service QoS. Adaptive modulation and code (AMC) techniques are potential candidates to face these effects by changing its parameters (reducing the number of symbol in the constellation of the modulation scheme or adding redundancy bits) according to channel conditions thus improve the quality of service. The M-QAM (M-Quadrature Amplitude Modulation) and M-PSK (M-Phase Shift Key) modulation and FEC (Forward Error Correction) protocol have been considered in this study due to its extensive use in adaptive techniques. The channel is modeled by Gilbert-Elliot method (GE), in which the probability of packet error was evaluated. In this paper we analytically studied the performance of adaptive modulation and adaptive FEC techniques in Rayleigh fading channels. The results show that the adaptive FEC performs better than the adaptive modulation when the ratio Es / No are high value and worse performance otherwise. A hybrid technique has also studied where the two techniques are combined. As a result, the performance of this technique is higher than that obtained with adaptive modulation (without code) or adaptive FEC (with fixed modulation). The comparison criteria which have been used are: the throughput, the average time to transmit a packet and the PER (Packet Error Rate).